2021
DOI: 10.1002/cam4.4125
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic factors that influence prognosis and survival outcomes in men with metastatic castration‐resistant prostate cancer treated with Radium‐223

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Several studies have reported composite prognostic scoring methods aimed at identifying patients that may benefit most from 223 Ra therapy (59)(60)(61)64). A composite score derived from combining baseline Hb ≥ 120 g/L, total ALP ≤ 110 U/L and ECOG PS 0-1 identified patients with a low-, intermediate-or high-risk of death (composite score 2, 3-4 and 5-6, respectively; median OS 23, 8, and 5 months) (60).…”
Section: Composite Markersmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported composite prognostic scoring methods aimed at identifying patients that may benefit most from 223 Ra therapy (59)(60)(61)64). A composite score derived from combining baseline Hb ≥ 120 g/L, total ALP ≤ 110 U/L and ECOG PS 0-1 identified patients with a low-, intermediate-or high-risk of death (composite score 2, 3-4 and 5-6, respectively; median OS 23, 8, and 5 months) (60).…”
Section: Composite Markersmentioning
confidence: 99%
“…Multivariate analyses have found various factors to be associated with survival outcomes. Baseline Hb was found to be prognostic of OS ( 59 ) and elevated baseline Hb (≥ 120 g/L) was associated with increased OS ( 60 ), whereas low baseline albumin (< 35 g/L) ( 61 ) and elevated PSA (> 80 μg/L) ( 61 ) were associated with poor OS. Similarly, other factors prognostic of OS include baseline neutrophil-to-lymphocyte ratio ( 28 ), baseline lactose dehydrogenase ( 62 ) [with elevated lactose dehydrogenase associated with shorter OS ( 41 )] and higher baseline ALP ( 28 ) [with ALP > 150 U/L associated with poor OS ( 61 )].…”
Section: Development Of Response Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies previously investigated many parameters potentially able to improve patient’s selection since baseline [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, most of them remained inconclusive since none of the identified clinical or biochemical biomarkers has been validated as a unique and reliable selection tool.…”
Section: Introductionmentioning
confidence: 99%